2019
DOI: 10.1101/819276
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain networks processing temporal information in dynamic facial expressions

Abstract: Acknowledgments:We would like to thank Lucas Tamarit for his help with the FACSGen program. Finally, we are grateful to Prof. Karl Friston for his guidance in the DCM analysis. 2 AbstractPerception of emotional expressions in faces relies on the integration of distinct facial features. We used fMRI to examine the role of local and global motion information in facial movements during exposure to novel dynamic face stimuli. We found that synchronous expressions distinctively engaged medial prefrontal areas in th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Although some studies have observed an uncanny valley effect in humans and monkeys (Saygin et al, 2012;Siebert et al, 2020;Steckenfinger and Ghazanfar, 2009), they do not necessarily negate the validity of using avatars as potential social stimuli. The dip of the uncanny valley curve depends on the stimuli and may be related to ambiguous categorization, less realistic appearance, or asynchronous emotional, motor, and audio cues (Burleigh et al, 2013;Cheetham et al, 2015;Skiba and Vuilleumier, 2020). For example, in macaques, the most naturalistic avatars have been found to elicit similar facial expressions as videos of real monkeys (Siebert et al, 2020).…”
Section: Level 3: Dynamic and Contingent Social Stimulimentioning
confidence: 99%
“…Although some studies have observed an uncanny valley effect in humans and monkeys (Saygin et al, 2012;Siebert et al, 2020;Steckenfinger and Ghazanfar, 2009), they do not necessarily negate the validity of using avatars as potential social stimuli. The dip of the uncanny valley curve depends on the stimuli and may be related to ambiguous categorization, less realistic appearance, or asynchronous emotional, motor, and audio cues (Burleigh et al, 2013;Cheetham et al, 2015;Skiba and Vuilleumier, 2020). For example, in macaques, the most naturalistic avatars have been found to elicit similar facial expressions as videos of real monkeys (Siebert et al, 2020).…”
Section: Level 3: Dynamic and Contingent Social Stimulimentioning
confidence: 99%